Delayed Reproduction, Injury, and Regeneration of Testes in Out-of-Season Breeding of Largemouth Bass (Micropterus nigricans) - Kuo He; Yi Yang; Zhihong Li; Haoxiao Yan; Kaige Song; Qiao Liu; Liulan Zhao; Song Yang (MDPI AG, 2024)
Out-of-season breeding is an effective method for addressing seasonal shortages of fry in aquaculture species such as largemouth bass (LMB) for year-round production. Off-season breeding of LMB can be achieved by subjecting breeding LMB to prolonged low-temperature conditions; however, this can alter reproductive rhythms, affecting the quality of their sperm and leading to a decrease in reproductive efficiency. Therefore, it is crucial to investigate issues such as the damage to the testes and the related mechanisms caused by low-temperature stress during out-of-season breeding. In this experiment, we assessed the changes in the testes during this time in LMB by comparing reproductive rhythms, testicular histomorphology, ultrastructure, antioxidant capacity and apoptosis. We synthesized measurements of LMB from three identically treated cement ponds and fish exposed to water temperatures of 13-16 °C to assess the changes in the testes. The results showed that (1) out-of-season reproduction delayed sperm production and promoted sperm redevelopment in LMB, various hormone levels have changed over time (e.g., LH, FSH, and T). (2) The head plasma membrane of LMB spermatozoa was separated, and the middle mitochondria were swollen. (3) The expression levels of antioxidant enzymes (cat, sod, and gpx) were upregulated, and oxidative stress occurred in LMB. (4) The expression levels of apoptosis genes (e.g., bax, bcl2, and caspase3) were upregulated, and apoptosis occurred in LMB due to off-season breeding. Moreover, important genes of the mitochondrial apoptosis pathway (bid, CYT-C) were upregulated, indicating that spermatozoan apoptosis in LMB was probably achieved through the mitochondrial apoptosis pathway. These results suggest the delays, damage, and regeneration of LMB testes. Our findings provide new insights into the molecular mechanisms that trigger changes in sperm quality during out-of-season breeding in fish.